Survey on the perception and use of electronic books among it students / Roesnita Ismail - Roesnita , Ismail (2005)
This study investigates the possible factors that might be related to the perception and use of electronic books (e-books) among undergraduates at the Faculty of Computer Science and Information Technology (FCSIT), University of Malaya (UM). It focuses on identifying the usage pattern of e-books especially on how, when, where and why the students use or not use the e-books. This exploratory study employs the descriptive survey method and uses the questionnaire as the data collection instrument. The general framework of student’s e-book use environment and its four major factors are presented in detail. The findings revealed that there was positive acceptance of e-books among IT students, although the use of e-books was still limited. E-book users were computer and technology literate but the hours spent on accessing the Internet per week had no influence on the use of e-books. Most of them used the UM Library web site as their main gateway to access e-books from the faculty’s computer labs or homes. E-book uses were mainly for writing assignments or research projects and reference. Users indicated online availability, fast and easy access to new titles as their main reasons for using e-books. In contrast, non-users considered preference for paper format as the main barrier for not using e-books service. The users and non-users preferred to read a prined textbook, however, most of them preferred to refer an online reference book. Implications of the findings, suggestions for future studies and recommendations for positive actions to be taken by library and librarians were also suggested.